2009
DOI: 10.1208/s12248-009-9115-2
|View full text |Cite
|
Sign up to set email alerts
|

“Fit-for-Purpose” Method Validation and Application of a Biomarker (C-terminal Telopeptides of Type 1 Collagen) in Denosumab Clinical Studies

Abstract: Abstract. Biomarkers are used to study drug effects, exposure-response relationships, and facilitate early decision making during development. Denosumab, a fully human monoclonal antibody against receptor activator of nuclear factor-κB ligand, profoundly inhibits bone resorption. C-terminal telopeptides of type I collagen (CTx), a bone resorption biomarker, provides early indications of denosumab effectiveness and informs protracted clinical outcomes (e.g., bone mineral density). Because of the dynamic relatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 16 publications
0
28
0
Order By: Relevance
“…therefore, bone biochemical markers are extremely useful to predict the long-term responsiveness to treatment after a few weeks. early changes in bone biochemical markers, particularly those reflecting bone resorption, such as ctX, predict the longterm rate of bone loss as well as the risk of incident fracture (40)(41)(42)(43)(44)(45)(46)(47)(48)(49). the magnitude of the reduction in markers of bone resorption observed in the foregoing study is less than that observed following therapeutic doses of strong inhibitors of bone resorption such as bisphosphonates (44,46,47).…”
Section: Participants and Designmentioning
confidence: 82%
“…therefore, bone biochemical markers are extremely useful to predict the long-term responsiveness to treatment after a few weeks. early changes in bone biochemical markers, particularly those reflecting bone resorption, such as ctX, predict the longterm rate of bone loss as well as the risk of incident fracture (40)(41)(42)(43)(44)(45)(46)(47)(48)(49). the magnitude of the reduction in markers of bone resorption observed in the foregoing study is less than that observed following therapeutic doses of strong inhibitors of bone resorption such as bisphosphonates (44,46,47).…”
Section: Participants and Designmentioning
confidence: 82%
“…In these For exploratory assays, the new lot of calibrator material should show similar results as the previous lot as suggested in Table V. In the event the performance of the new lot of material differs from the reference lot, we recommend obtaining another replacement lot (if available), normalizing the new lot concentration to the original lot using a correction factor (29), or value assignment (23,31,32). For treatment decision-making assays, multiple lots (a minimum of three) should be tested as early as possible and a normalization strategy via value assignment should be considered.…”
Section: Recommendations For Biomarker Calibrator Materials Characterimentioning
confidence: 99%
“…Trending of results for biomarker assays is already used by many to assess QC stability and assay robustness [13]. future science group…”
Section: Trend Analysismentioning
confidence: 99%
“…Inclusion of such samples affords confidence that comparable results are produced each time the assay is utilized and would detect upward or downward trends in concentration assuming that stability of such samples can be determined. Such an approach is described by Wang et al [13], where both high and low 'authentic samples' (incurred samples) were analyzed in each sample analysis run. Furthermore they were able to demonstrate reliability and robustness for the method despite two different reference material lots being used over 3 years in 12 clinical studies.…”
Section: Trend Analysismentioning
confidence: 99%